Variation in protein precipitation and phenolic content within and among species across an elevational gradient in subarctic Sweden - Olofsson, Elin (SLU/Dept. of Forest Ecology and Management, 2010)
This project investigated how elevation and vegetation type influences variation in plant litter phenolic content and protein precipitation capacity among and within common plant species for two different vegetation types, heath and meadow, in a subarctic ecosystem in the Abisko region of northern Sweden. As nutrient availability generally decreases with increasing elevation as a result of decreasing temperature, I hypothesised that phenolic content would increase with elevation and be higher on the heath than the meadow. To test this, the total phenolic content and protein precipitation capacity was estimated in leaf litter from 13 species in both heath and meadow vegetation across an elevational gradient ranging from 500 to 1000 meters above sea level (m.a.s.l.) in the study region. The results showed that elevation and vegetation type both had a strong impact on both variables. Total phenolic concentrations decreased with elevation for the meadow, and were greater for the heath than the meadow. Moreover, there was a general trend of decline in protein precipitation with increasing elevation for both vegetation types. Further, species that dominated at higher elevations produced litter with lower phenolic concentrations and protein precipitation capacity than did those species that dominated at lower elevations. My results are inconsistent with my hypothesis as well as with previous studies that have suggested a negative relationship between phenolic content and nutrient availability. They also highlight the need for an improved understanding of what factors drive phenolic production in plant litter, both within subarctic ecosystems and more generally.